Detection of haemoglobin S using multiplex ligation-dependent probe amplification and flow-through hybridization techniques: experience in a tertiary hospital - Wee, SY; Hafiza Alauddin; Raja Zahratul Azma Raja Sabudin; Norunaluwar Jalil; Azlin Ithnin; Malisa MY; Qistina WN; Ainoon O (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Haemoglobin S (HbS, α2β26GluVal) is a variant haemoglobin resulted from GAGGTG mutation on codon 6 of HBB gene. HbS haemoglobinopathy is uncommon in Malaysia and mainly seen in immigrants. However, Malaysian Indians and Malays are rarely affected. This study reviewed the laboratory findings of patients with HbS and the utilization of multiplex ligation-dependent probe amplification (MLPA) and flow-through hybridization (FTH) in the detection of HbS mutation. HbS was identified and quantified by high performance liquid chromatography (HPLC), capillary electrophoresis (CE) and cellulose acetate gel electrophoresis. Molecular analysis was performed using MLPA, FTH and Sanger Sequencing. Two Africans, three Malays and two Indian individuals aged between 2-31 years were identified from our laboratory. Five patients were homozygous HbS, one was compound heterozygous HbS/β-thalassemia and one was a carrier of HbS. The patients with homozygous HbS had their haemoglobin (Hb) ranging from 7.4-10.2 g/dL with HbS and HbF levels of 58.3-94.7% and 1.5-35.5%, respectively. The Hb of compound heterozygous HbS/β-thalassaemia patients was 5.8 g/dL and was normal in heterozygous HbS. HbS, HbF and HbA2 levels for the HbS/β-thalassaemia and the carrier were 67%, 27.2% and 4.2%, and 38.6%, 0.1% and 2.8%, respectively. Both MLPA and FTH successfully detected HbS mutation in all cases but only FTH could identify the zygosity of the HbS mutation together with underlying concomitant β-thalassaemia in a single test.